2003
DOI: 10.1380/ejssnt.2003.20
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Oxygen with the Polar HfC(111) Surface: Angle-Resolved Photoemission Study

Abstract: Angle-resolved photoemission spectroscopy utilizing synchrotron radiation has been used to study the adsorption state of oxygen on a HfC(111) surface. Oxygen adsorbs dissociatively on the HfC(111) surface at room temperature forming a (1 × 1) overlayer at the saturation coverage. The two-dimensional band structure of the chemisorption bonding states formed through the hybridization of O 2p and Hf 5d orbitals (O 2p-derived states) is measured for the HfC(111)(1 × 1)-O surface. It is found that the 2pz-derived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Our previous study on the oxidation of the HfC(111) surface has revealed that the HfC(111) surface is very reactive to O 2 adsorption; O 2 adsorbs dissociatively with the sticking probability of approximately 1 [24]. However, on the (111) surface, the adsorptiom saturates when the (1 × 1) overlayer is completed (2 L), and the oxidation of the substrate below the surface does not occur [24]. It is considered to be due to the fact that the HfC(111) surface is covered with an Hf layer.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study on the oxidation of the HfC(111) surface has revealed that the HfC(111) surface is very reactive to O 2 adsorption; O 2 adsorbs dissociatively with the sticking probability of approximately 1 [24]. However, on the (111) surface, the adsorptiom saturates when the (1 × 1) overlayer is completed (2 L), and the oxidation of the substrate below the surface does not occur [24]. It is considered to be due to the fact that the HfC(111) surface is covered with an Hf layer.…”
Section: Resultsmentioning
confidence: 99%